Optimizing the PVD TiN thin film coating as parameters on aerospace AL7075-T6 alloy for higher coating hardness and adhesion with better tribological properties of the coating surface - Zalnezhad, E.; Sarhan, Ahmed Aly Diaa Mohammed; Hamdi, M. (2013)
An optimization study on the parameters of titanium nitride coating on aerospace Al7075-T6 alloy, using magnetron sputtering technique is presented. The effects of the temperature, DC bias voltage, rate of nitrogen, and DC power on the surface hardness, adhesion, surface roughness, and microstructure of the coated samples are investigated. Taguchi optimization method is used with the orthogonal array of L16 (44). However, to obtain the most optimum parameters for the best surface hardness, adhesion, and surface roughness, the signal to noise (S/N) response analysis method is implemented. Finally, the confirmation tests were carried out to show the improvement using the best parameters combination obtained from the optimization process. The improvement of 14 in surface hardness, 4.15 in adhesion, and 9.43 in surface roughness are achieved.